Decision Support System (DSS) for MSMA Integrated Stormwater Management Ecohydrology for Sustainable Green Infrastructure - Sidek L.M.; Mohiyaden H.A.; Haris H.; Basri H.; Muda Z.C.; Roseli Z.A.; Norlida M.D. (Institute of Physics Publishing, 2023)
Artificial intelligence; Catchments; Decision making; Expert systems; Rivers; Runoff; Storm sewers; Storms; Urban planning; Water pollution; Water quality; Water treatment; Decision support system (dss); Green infrastructure; Hydrological cycles; Practical experience; Rapid urbanizations; Storm-water managements; Stormwater best management practices; Stormwater pollutants; Decision support systems; automation; catchment; decision support system; drainage water; ecohydrology; expert system; greenspace; infrastructural development; organic pollutant; river; sustainable development; urban area; urbanization; wastewater; water management; water quality